2020
DOI: 10.1101/2020.12.24.424256
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivovisualization of pig vagus nerve ‘vagotopy’ using ultrasound

Abstract: BackgroundPlacement of the clinical vagus nerve stimulating cuff is a standard surgical procedure based on anatomical landmarks, with limited patient specificity in terms of fascicular organization or vagal anatomy. As such, the therapeutic effects are generally limited by unwanted side effects of neck muscle contractions, demonstrated by previous studies to result from stimulation of 1) motor fibers near the cuff in the superior laryngeal and 2) motor fibers within the cuff projecting to the recurrent larynge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…On the other hand, the swine vagus has 5-10 times more fascicles than the human vagus and accordingly smaller fascicle diameters (Suppl. Figure 1), thereby representing a appropriate and challenging anatomical substrate for testing methods and technologies for selective vagus neuromodulation [2, 11, 15, 45, 46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the swine vagus has 5-10 times more fascicles than the human vagus and accordingly smaller fascicle diameters (Suppl. Figure 1), thereby representing a appropriate and challenging anatomical substrate for testing methods and technologies for selective vagus neuromodulation [2, 11, 15, 45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Resolving the selectivity profile on a single subject basis requires real-time or semi-real time methods. Recently, it was reported that the large-scale fascicular structure of the swine vagus can be visualized with noninvasive, high resolution ultrasound imaging [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-D plane-by-plane volumetric B-mode images were collected ( Figures 1D–F ). Data associated with this study ( Settell et al, 2021 ), were collected as part of the Stimulating Peripheral Activity to Relieve Conditions (SPARC) program and are available through the SPARC Portal (RRID: SCR_017041) under a CC-BY 4.0 license.…”
Section: Methodsmentioning
confidence: 99%
“…For example, there is evidence for somatotopic organization of the pseudounipolar cell bodies of sensory afferents in nodose ganglia. However, more recent research has suggested that this organization may only be present in pigs but not in humans ( Settell et al, 2021 ). Large differences also exist in the diameter of the VN between species; this should be considered when evaluating the translational potential of VNS techniques demonstrated in small animals (such as rodents).…”
Section: Introductionmentioning
confidence: 99%